The Potential of Portable AR in Physics Education: A Study on Student Perceptions - Anselmo, Charlie T.; Saet, Artemio B.; Magleleong, Angelica P.; Cagayan, Apol Joy D.; Corpuz, Fely T. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Integrating portable augmented reality (AR) into physics education has the potential to enhance student engagement and learning outcomes. This study investigates students' perceptions of the appeal and effectiveness of the Traveling Virtual Lab (TVL), a solar-powered AR learning kit designed to improve physics education in the Philippines. A quantitative research design was employed, utilizing the "Student Acceptance of Virtual Laboratory questionnaire" adapted from Park (2009). The sample consisted of 58 students, with a balanced gender distribution and a majority at the tertiary-education level. Descriptive and inferential statistical analyses were performed to address the research questions. The results indicate that students perceive TVL as appealing and effective for learning physics concepts, with mean ratings of 3.9 for both variables. No significant differences were found in perceptions based on gender or grade. This study highlights the potential of portable AR to enhance physics education by providing immersive and interactive experiences that can visualize complex concepts and overcome resource constraints. However, challenges remain, including technological accessibility and the need for training teachers. These findings contribute to the growing body of literature on AR in education and have implications for the development and implementation of virtual laboratory technologies, particularly in resource-constrained settings. Future research should focus on addressing implementation challenges and exploring the long-term impact on student learning outcomes.